The pulmonary arterial hypertension quality enhancement research initiative: comparison of patients with idiopathic PAH to patients with systemic sclerosis-associated PAH. Issue 2 (13th October 2011) - Clements, Philip J; Tan, Mary; McLaughlin, Vallerie V; Oudiz, Ronald J; Tapson, Victor F; Channick, Richard N; Rubin, Lewis J; Langer, Anatoly
Abstract : Objective: The objective of this report is to compare baseline, management and survival characteristics in idiopathic pulmonary arterial hypertension (IPAH) with systemic sclerosis-associated pulmonary arterial hypertension (SSc-APAH) using data from the prospectively enrolled PAH Quality Enhancement Research Initiative. Methods: Between August 2005 and July 2007, patients with IPAH and SSc-APAH were enrolled across 60 US sites and followed up for 3 years. Data on diagnostic tests, clinical variables, pulmonary arterial hypertension (PAH) medication and outcomes were recorded. Results: With some exceptions, baseline clinical and laboratory characteristics were similar between the 279 patients with IPAH and the 228 with SSc-APAH. Patients with SSc-APAH were older at the time of PAH diagnosis, were more likely to be female and were antinuclear antibody positive. Patients with SSc-APAH had poorer spirometric results. During the 3-year follow-up, both groups were managed with prostacyclin and prostacyclin analogue treatment, endothelin receptor antagonists and phosphodiesterase type 5 inhibitors (PDE5i) singly or in combination. At 3 years, patients with SSc-APAH were more likely to be treated with PDE5i alone or with an endothelin receptor antagonist. Patients with SSc-APAH had a significantly lower survival rate compared to patients with IPAH (60% vs 77%, p<0.0001). Conclusions: The cohort with SSc-APAH was older, was more severely ill, was more likely to be female, was managed with PDE5i and had reduced 3-year survival compared with the cohort with IPAH.